USE OF MODERN INFORMATION EDUCATION TECHNOLOGIES IN UKRAINE - ANTONOVA, Liudmyla; BЕLOZERTSEV Vasyl; HARAKOZ, Lilya (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article analyzes the use of modern information technologies in Ukraine. It has been established that the modern education system is closely dependent on financing and investing in information technologies. It was observed that the scientific and technical progress, the computerization of society of the 21st century led to the deepening of modern informational and innovative processes taking place in society. The activation of the use of information technologies in education was revealed, especially with increasing attention to the organization of learning in mixed and distance formats. An increasing number of educational institutions of various levels of education are implementing information and educational technologies that allow increasing the efficiency of educational services. Special attention is needed not only to the professional training of teachers, but also to their ability to use the latest technologies in their professional activities. In recent years, Ukraine has experienced a massive introduction of information technologies into education. First of all, the introduction of information technologies into the educational process, which involves their use in the study of individual subjects or disciplines. The information society determines the transformation of the education system. The rapid, efficient and global transfer of knowledge in recent years has created a new national and international basis for cooperation and teamwork. The growing role of information technologies in the development of education requires an active response to the challenges of the information society. Already now, new requirements are being put forward for the basic qualifications of specialists and for their knowledge of the consequences of the introduction of information technologies.